Antifungal Potential of Propolis Extract Against Candida Albicans: Literature Review - Olivia Maheswari Soerjanto; Pepy Dwi Endraswari; Abdul Khairul Rizki Purba (International Journal of Science and Society, 2023)
The increasing rate of Candida resistance against pharmacological drugs has become a particular focus in the medical world, especially considering the high mortality rate due to systemic infections caused by Candida. It is evident that the urgency of developing alternative medicines applies for potential natural ingredients like propolis. This literature review aims to discuss the antifungal effectiveness of propolis against C. albicans which is described by the MIC (minimum inhibitory concentration) and MFC (minimum fungicidal concentration) values from the test results. The search for relevant literature was conducted using the Google Scholar, ScienceDirect, and PubMed databases using the keywords "Propolis AND MIC AND MFC AND Candida albicans". There were nine articles that had been adjusted to the inclusion and exclusion criteria based on the PICOS Framework. The propolis in the article uses various solvents with various extraction methods, and various antifungal tests are carried out on standardized and clinical isolates of C. albicans. All the reviewed articles consistently support the finding that propolis has a strong ability to inhibit the growth and kill the pathogenic fungus C. albicans. The lowest MIC value found was 0.06 μg/mL, and the MFC value was 0.121 μg/mL. Propolis has potential as an ingredient that can be further developed as a non-pharmacological therapy for pathogenic fungal infections.